Efficiency of services in CEE countries—case study of Poland and Belarus - Skąpska, Elżbieta; Rollnik-Sadowska, Ewa (Economics and Business Review, 2020)
The aim of the paper is to identify determinants of the efficiency of servicecompanies from two Central and Eastern European (CEE) countries4—Poland andBelarus. These transition economies represent different economic and systemic conditions.That is why it is worth analyzing whether external conditions determine internalefficiency factors in service companies. In order to achieve that aim quantitativeresearch was conducted among 305 Polish and Belarusian service enterprises. Theresearch results presented significant differences in responses between the two countries.For Polish enterprises the main determinants of efficiency were above all connectedwith competent and skilled staff. Belarussian companies regarded as efficiencyfactors which determine the demand level by means of access toward foreign marketsand possibilities of internationalization. It proves that CEECs are not homogeneousand they represent different levels of economic development as well as the differentconditions of running a business.